Grenada : First Review Under the Poverty Reduction and Growth Facility Arrangement, Request for Waiver of Performance Criterion, Financing Assurance Review, Request for Rephasing and Extension of the Arrangement, and Request for Augmentation-Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
The staff report for the First Review Under the Poverty Reduction and Growth Facility (PRGF) Arrangement highlights Grenada's economic performance in many respects. The time needed to address the unregulated bank, as well as fiscal slippages and the slow pace of structural reform, delayed completion of the first PRGF review. The program entails some risks, particularly with respect to bank restructuring costs, expenditure control, implementation capacity, and natural disasters. The government is considering a concessional loan from the Export-Import Bank of China to finance the construction of a port and marina.